Small Breast Cancer (≤ 5 mm): Ultrasonographic Features and Clinical and Pathological Characteristics - Hye Young Kwon (대한영상의학회지, 2019)
Purpose To identify differences in ultrasonography (US) feature, clinical and pathological characteristics including immunohistochemical characteristics between small breast cancer (pathologic size ≤ 5 mm) and large breast cancer (> 5 mm). Materials and Methods A total of 528 invasive breast cancer lesions in 475 patients were included. US features with clinical and pathological characteristics were evaluated according to pathologic size. US Breast Imaging-Reporting and Data System findings and final assessments were recorded for each lesion. Standard references were based on surgical pathologies. Results Of 528 invasive breast cancer lesions, 62 were small breast cancers. Small breast cancers showed a higher rate of oval, round shape, parallel orientation; circumscribed margin; and iso/solid and cystic echo pattern, with no posterior feature. The final assessment of category 4 was also a dominant factor in small breast cancer. Early stage, asymptomatic state, and extensive ductal carcinoma in situ component were associated with small breast cancers. Conclusion Our results show that small breast cancers have less suspicious US features than large breast cancers.